AWARENESS REGARDING MODES OF TRANSMISSION AND RELATED MISCONCEPTION ABOUT HIV/AIDS AMONG SECONDARY SCHOOL GOING FEMALES OF PUBLIC AND GOVT SCHOOLS - Mohan, Chhabi; Chachra, Jayshree; Nigam, Seema (Indian Journal of Community Health, 2010)
.Research Question: What is the level of awareness about different modes of transmission and related misconception about HIV/AIDS among secondary school going females of public and Govt. Schools of Kanpur city. Study Area: Public and Govt. Schools of Kanpur city. Participatns: 120 Govt. and 120 Public secondary School females students. Results: 100% Public school female students knew about heterosexual mode of transmission of HI V/AIDS as compared to 80% of Govt. School students. Among Public School students knowledge about transmission of HIV/AIDS by contaminated needle and syringe intravenous drug abuse, blood transfusion and mother to child was known to almost 80% student. Among Govt. School students except for knowledge about transmission by contaminated needle and syringe (60%) and mother to child transmission (55%) the other modes were poorly known (<50%).